2006
DOI: 10.1103/physrevb.74.245104
|View full text |Cite
|
Sign up to set email alerts
|

Green’s function of the Holstein polaron

Abstract: We present a novel, highly efficient yet accurate analytical approximation for the Green's function of a Holstein polaron. It is obtained by summing all the self-energy diagrams, but with each selfenergy diagram averaged over the momenta of its free propagators. The result becomes exact for both zero bandwidth and for zero electron-phonon coupling, and is accurate everywhere in the parameter space. The resulting Green's function satisfies exactly the first six spectral weight sum rules. All higher sum rules ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
179
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(186 citation statements)
references
References 58 publications
7
179
0
Order By: Relevance
“…Similar to the Holstein model, the large-to-small polaron transition occurs at lower λ for increasing α. 23,38 At weak and moderate coupling, the qp weight and the effective mass (not shown) in the breathing-mode model are much less sensitive to an increase in α, than is the case for the Holstein polaron. This suggests that breathing-mode polarons should be better charge carriers than the Holstein polarons, in this regime.…”
Section: A Low-energy Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the Holstein model, the large-to-small polaron transition occurs at lower λ for increasing α. 23,38 At weak and moderate coupling, the qp weight and the effective mass (not shown) in the breathing-mode model are much less sensitive to an increase in α, than is the case for the Holstein polaron. This suggests that breathing-mode polarons should be better charge carriers than the Holstein polarons, in this regime.…”
Section: A Low-energy Statesmentioning
confidence: 99%
“…In 1D we can investigate accurately and efficiently not only ground-state (GS) properties, but also some excited state properties. For the Holstein model, it was found that polaron properties are qualitatively similar in different dimensions, 23,38 but with a sharper large-to-small polaron crossover in higher dimensions. We will show that a sharp crossover is already present in the 1D model, and we expect less dimensionality effects in the breathing-mode Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-We use the momentum average (MA) approximation to carry out this study. MA was shown to be very accurate in describing GS polaron properties for the linear Holstein model, where it satisfies exactly multiple sum rules and becomes asymptotically exact in the limit of strong coupling [14]. It is straightforward to verify that all these considerations remain valid for the generalized Holstein model: H = H el + H ph + H el-ph , defined as follows.…”
mentioning
confidence: 99%
“…From this we can extract all the polaron's GS properties [14]. We rewrite the quadratic Hamiltonian as…”
mentioning
confidence: 99%